Adolescent girls' recommendations for designing Human Papillomavirus Vaccination Program in Pakistan. (20th October 2021) - Ali, RF; Offeddu, V; Siddiqi, DA; Mirza, A; Naz, N; Abdullah, S; Lim, JM; Kembhavi, G; Tam, CC; Chandir, S
Abstract:  : In Pakistan, cervical cancer is the third most frequent cancer among women. Most cases are caused by sexually-acquired infection with human papillomaviruses (HPV). Vaccination of adolescent girls against HPV significantly reduces the incidence of cervical cancer. HPV vaccination is available in Pakistan, but plans to develop a HPV vaccination program are currently at a very early stage. We conducted a formative study to explore adolescent girls' perspectives on HPV and cervical cancer, and collected their recommendations for implementing an HPV vaccination program. We conducted qualitative focus group discussions (FGDs), with unmarried adolescent girls aged 16-19 years, residing in Karachi. We conducted four FGDs with 12 participants each. The topic guide assessed i) girls' knowledge of cervical cancer and HPV vaccination, ii) vaccination decision-making dynamics within families, and iii) factors girls would consider essential for the successful implementation of HPV vaccination program. Overall, participants displayed a positive attitude towards the HPV vaccine. However, many basic concepts related to female reproductive health were unfamiliar to them. Female relatives were indicated as girls' preferred point of contact for discussions on HPV and cervical cancer, but fathers were portrayed as the definitive decision-making authority on vaccination. Girls gave critical input for the development of a HPV vaccination program. Eligible girls should be recruited through individual household visits and the vaccine should be administered at community-based camps, which would ensure both good accessibility and a large outreach. A solid foundation of trust between girls' families, program managers, and other stakeholders emerged as a key asset for the program's success. Adolescents demonstrated great capacity and shared recommendations for a future program's acceptability. Integrating their perspectives will be essential to design an effective program in local context. Key messages: Adolescent girls' perspectives should be incorporated to develop context-specific recommendations for the implementation of a HPV vaccination program. Community-based camps and household visits by adolescent girls to recruit the target population could potentially increase program penetration among communities.